Literature Review: Factors Causing Anaemia in Adolescent Girls - Endang Purwati, Ayu; Nurherliyany, Metty; Solihah, Rosidah; Wulan Ratna Dewi, Sri (LPPM STIKes Muhammadiyah Ciamis, 2024)
Introduction: Anaemia is one of the problems that often occurs in adolescent health, especially adolescent girls. the prevalence of anaemia in adolescents aged 15-24 years is 32%, meaning that it is estimated that as many as 3-4 adolescents out of a total of 10 adolescents suffer from anaemia. Adolescents are vulnerable to health risks due to rapid body development and adequate nutritional intake is one of the factors that can affect nutritional status in adolescents, the results of the study explained that the lack of nutritional intake has an impact on the nutritional status of adolescents.the impact of anaemia experienced by adolescent girls will make adolescents feel lethargic, can reduce memory ability so that academic achievement is not optimal and can also have a more serious impact, considering that they are prospective mothers who will become pregnant and give birth to babies, thereby increasing the risk of maternal death, giving birth to premature babies and low birth weight. Translated with DeepL.com (free version). Objective: This study aims to determine the factors that cause anaemia in adolescent girls. Method: Literature study of five scientific articles obtained through google scholar database published between 2028 and 2023. Result: All studies show that there are several factors that cause anaemia in adolescent girls. Conclusion: Factors that can cause anaemia in adolescent girls include menstrual conditions, unbalanced nutritional intake, eating and drinking patterns, non-compliance with Fe tablet consumption and lack of knowledge.